2014
DOI: 10.1186/preaccept-7344673251342033
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of exclusive breastfeeding against hand, foot and mouth disease

Abstract: BackgroundInfants who are exclusively breastfed receive natural protection against some infectious agents. This study examined whether there was protective effect of exclusive breastfeeding on the occurrence of hand, foot and mouth disease, which was an emerging infectious disease among children in China.MethodsA community-based case–control study was carried out among children age 4 years or younger in Guangdong Province, China. Cases were newly diagnosed hand, foot and mouth disease. Controls were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is surmised that the antibodies existing in the neonatal blood from maternal blood and breast, which decline with the age growing, might provide protection against the infection. [ 8 ] The WBC, the PCT, and also the CRP, were usually normal or increased slightly, which indicated that the infection was mild and almost impossibly exacerbated. [ 9 ] Although the 5 cases we met were full-term babies, HFMD also came across preterm babies with an atypical course.…”
Section: Discussionmentioning
confidence: 99%
“…It is surmised that the antibodies existing in the neonatal blood from maternal blood and breast, which decline with the age growing, might provide protection against the infection. [ 8 ] The WBC, the PCT, and also the CRP, were usually normal or increased slightly, which indicated that the infection was mild and almost impossibly exacerbated. [ 9 ] Although the 5 cases we met were full-term babies, HFMD also came across preterm babies with an atypical course.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, younger children (<6 mo) are more likely to develop asymptomatic EV‐A71 infections, which may be due to the protection of maternal antibody against symptomatic EV‐A71 infections . Breastfeeding has been shown to have protective effects against HFMD in young children …”
Section: Host Immune Responses To Ev‐a71 Infectionmentioning
confidence: 99%
“…16,57 Breastfeeding has been shown to have protective effects against HFMD in young children. 58 Neutralizing antibodies bind and neutralize virus efficiently, thus preventing further progression of disease. Humoral immune responses are elicited when clinical symptoms appear, and 80% of HFMD patients became positive for neutralizing antibodies against EV-A71 one day after the onset of illness.…”
Section: Protective Humoral Immune Responsesmentioning
confidence: 99%
“…The benefits of breast-feeding for both mother and child have been widely recognized, serving as a nutritional and energy supplement, helping to prevent infections and diseases, and promoting maternal well-being ( 2 ) . Breast-feeding helps reduce the risk for breast and ovarian carcinoma and type 2 diabetes in mothers ( 3 ) , and EBF during the first 6 months of life reduces the risk of becoming overweight in the offspring ( 4 ) and can prevent such infections as rotavirus diarrhoea and hand, foot and mouth disease ( 5 , 6 ) . Globally, 37 % of infants younger than 6 months in low-income and middle-income countries receive EBF ( 7 ) .…”
mentioning
confidence: 99%